Estudo comparativo de métodos para a predição do consumo máximo de oxigênio e limiar anaeróbio em atletas - Mahseredjian, Fabio [UNIFESP] (1999)
The application of a battery of tests for evaluation of the physical aptitude in laboratory involves a series of highly sophisticated equipment, mainly when the objective is the determination of the aerobic potency (maximum oxygen uptake and anaerobic threshold). The equipment is of high financial cost and requests professionals with good technical and scientific knowledge to handle it, and also, it is impossible to use it in the application of tests in large scale. The analysis of the distance run in a certain period of time or, yet, the time used for a distance set previously, has been a lot used with the goal of estimating or reflecting the aerobic aptitude in children and in adults. The proposal of this study was to analyze the correlation of the Cooper test (CT) with the values of maximum consumption of oxygen (VO2 max) determined through direct method, besides the attempt of validating this field test and another test called the test of 4,000 meters, in anaerobic threshold (AT prediction). Sixty-three players of field soccer were appraised with ages between 15 and 20 years. The athletes were submitted to three tests, one of them was accomplished at the laboratory and the others in the athletics track, in a maximum period of seven days. The laboratory test consisted of the determination of the VO2 max and ventilatory anaerobic threshold (VAT), through analysis of the gaseous changes in a metabolic system analysis on a Vacumed (model CPX Silver edition) Imbramed ergometric treadmill (model ATL 10200), with measurement of the heart rate (HR) with the Polar brand (model Accurex Plus). The first field test followed the protocol determined by Cooper and the second one consisted of a race of 4,000 meters, when determination of the time spent for the preset course was made. The coefficient of linear correlation of Pearson was calculated (r) and the following results were obtained: The speed of LA showed direct significant correlation (r = 0.60 for p < 0.05) with the medium speed in CT. The speed of LA showed direct significant correlation (r = 0.74 for p < 0.05) with the medium speed in T 4000. The VO2 max determined by the direct method did not show significant correlation with the VO2 max (r = 0.23 for p < 0.05) determined through CT. The results suggest that the CT has not the precision required for the prediction of the VO2 max for this population and the possibility of its use for the field tests, like those performed in the present study, in order to obtain the prediction of the anaerobic threshold, and the 4,000 meters test presented larger precision than the CT when the goal is to predict the speed of the anaerobic threshold.